2016
DOI: 10.1177/0890334415597636
|View full text |Cite
|
Sign up to set email alerts
|

In-hospital Breastfeeding and Intention to Return to Work Influence Mothers’ Breastfeeding Intentions

Abstract: Exclusive breastfeeding in the hospital within the first 48 hours postpartum and intention to return to work influence how long a mother intends to breastfeed. Attention to these areas can be provided immediately postpartum to support exclusive breastfeeding and provide informational support on continuing to breastfeed/express milk upon return to work if the mother intends to return to work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 41 publications
0
21
3
1
Order By: Relevance
“…Also, because breastfeeding duration with a first child is a strong predictor of breastfeeding duration with subsequent children [20], providing adequate breastfeeding support to first time mothers can be beneficial beyond that pregnancy. In contrast to other studies [21,22] we found that returning to work was not associated with participants achieving their individual goals. However other studies have shown that return to work is associated with shorter duration of breastfeeding [23] and that maternity leave duration and full or part time work status are associated with US mothers' ability to meet breastfeeding intentions [24].A local study shows that approximately 85% of employed new mothers return to full-time employment before ten weeks postnatal and 88% work 40 hours per week or more [26].…”
Section: Discussioncontrasting
confidence: 99%
“…Also, because breastfeeding duration with a first child is a strong predictor of breastfeeding duration with subsequent children [20], providing adequate breastfeeding support to first time mothers can be beneficial beyond that pregnancy. In contrast to other studies [21,22] we found that returning to work was not associated with participants achieving their individual goals. However other studies have shown that return to work is associated with shorter duration of breastfeeding [23] and that maternity leave duration and full or part time work status are associated with US mothers' ability to meet breastfeeding intentions [24].A local study shows that approximately 85% of employed new mothers return to full-time employment before ten weeks postnatal and 88% work 40 hours per week or more [26].…”
Section: Discussioncontrasting
confidence: 99%
“…Also, because breastfeeding duration with a first child is a strong predictor of breastfeeding duration with subsequent children [20], providing adequate breastfeeding support to first time mothers can be beneficial beyond that pregnancy. In contrast to other studies [21,22] we found that returning to work was not associated with participants achieving their individual goals. However other studies have shown that return to work is associated with shorter duration of breastfeeding [23] and that maternity leave duration and full or part time work status are associated with US mothers' ability to meet breastfeeding intentions [24].A local study…”
Section: Discussioncontrasting
confidence: 99%
“…Provision of breastfeeding support from health workers, community health workers, peer supporters and others in the family or community have consistently been associated with improved feeding practices [ 11 , 17 , 18 ]. Returning to work after the birth of the infant is a major barrier to breastfeeding and is significantly associated with lower rates of breastfeeding, earlier cessation of breastfeeding, and mothers planning to return to work are less likely to plan to EBF [ 19 21 ].…”
Section: Introductionmentioning
confidence: 99%